FACTORS DRIVING THE USE OF SOCIAL MEDIA IN BUYING FASHION READY TO WEAR - Resi Sepsilia Elvera; Jerusalem, Mohammad Adam; Himmah, Laila Nurul; Mahanani, Chytra; Nurlita, Asri Andarini (Universitas Negeri Jakarta, 2024)
This research aims to see the driving factors for the use of social media in buying Ready To Wear clothing. The research population is Yogyakarta State University Fashion Management students who buy Ready To wear clothes. Samples were taken from participants who bought Ready To Wear clothing through social media. Data were collected using questionnaires and observations. The collected data were analyzed descriptively quantitatively using the Exploratory Factor Analysis (EFA) approach. The results showed that the level of use of social social media by students showed 3 factors, with a cumulative result of 76.201. This means that the variable use of social media has a significant level in purchasing ready to wear clothing, the factor is 76.20%. In the Ready To Wear Clothing Purchase Interest variable has a significant level in the purchase of ready to wear clothing, the factor is 76.20%